Supporting Black Students Through Their Science, Engineering, and Medicine Career Journeys: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Increasing the number of Black men and Black women who enter the fields of science, engineering, and medicine (SEM) will benefit the social and economic health of the nation. On May 2-3, 2022 the Roundtable on Black Men and Black Women in Science, Engineering, and Medicine of the National Academies of Sciences, Engineering, and Medicine convened a workshop to highlight promising financial and supportive services and programs throughout various stages of career development. Sessions followed student progression through the major stages of education and career development, and identified policies and practices that aim to mitigate and alleviate long-standing barriers to the full participation of Black students in SEM at the K–12, undergraduate, and graduate and professional levels.
Keywords: Education

Data Integration in Learning Health Care Systems for Traumatic Brain Injury: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Traumatic brain injuries (TBI) affect millions of Americans each year, causing symptoms that can be debilitating and long-lasting and resulting in physical, cognitive, emotional, and financial ramifications. The complexity and heterogeneity of TBI make it challenging to target the right interventions to the right patient at the right time. For those who do receive care, unlinked health records, fragmented care delivery, and gaps in medical surveillance means many questions remain unanswered about TBI prevalence, comorbidities, adverse outcome risk factors, and long-term outcomes. To help address this challenge, learning health care systems that bidirectionally exchange data and insights across clinical research, care services, and public health have been identified as key to improving patient outcomes. To help move the field forward, the National Academies Forum on Traumatic Brain Injury hosted a public workshop to explore the role of learning health systems in advancing TBI research and care. This Proceedings of a Workshop summarizes discussions and key messages from the workshop.
Keywords: Health and Medicine

Health Systems Science Education: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
The National Academies Global Forum on Innovations in Health Professional Education held a public workshop in November 2023. Speakers explored how health professional educators and providers with health systems science (HSS) training can prepare learners to work together within health systems, resulting in better patient care, improved population health, and enhanced health professional well-being. Organizers hosted a public pre-workshop in October 2023 to create a foundational understanding of HSS prior to their workshop.
Keywords: Education; Health and Medicine

Climate Intervention in an Earth Systems Science Framework: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
To consider how an Earth system science approach can inform research on climate intervention, The National Academies of Sciences, Engineering, and Medicine held a virtual workshop on June 20-22, 2023 titled Climate Intervention in an Earth Systems Science Framework. Individuals with a wide range of physical, ecological, and social sciences expertise explored climate interventions within the context of convergent research and the capacities of the National Science Foundation (NSF). The workshop drew on the National Academies report Next Generation Earth Systems Science at the National Science Foundation, which called upon NSF to pursue an Earth systems science initiative that emphasizes research on interconnections and feedback between natural and social processes; focuses on real-world problems; enhances the participation of social, engineering, and data scientists; and strengthens efforts to include diverse perspectives in research.
Keywords: Environment and Environmental Studies; Earth Sciences

The Science of Engaging Youth Lived Experience in Health Research, Practice, and Policy: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
There is a growing body of evidence demonstrating the value of incorporating youth voices in the development of research and programming aimed at supporting youth well-being. On October 11 and 12, 2023, the Forum for Childrens Well-Being hosted a two-day virtual public workshop, The Science of Engaging Youth Lived Experience in Health Research, Practice, and Policy, which was designed to explore the impacts of youth participatory methods including the potential for participatory methods to produce more effective, relevant, and sustainable interventions; the potential for participatory methods to engage historically marginalized communities among youth; the challenges of instituting participatory methods, including time, budgetary expenditures, and training; and opportunities to better incorporate participatory methods into research, systems, and programs for child well-being.
Keywords: Behavioral and Social Sciences

Mitigating Health Disparities in Brain Disorders Starting with Basic Science: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Despite increased attention paid to health equity in recent years, disparities in health outcomes and access to care persist across disease areas, including in central nervous system disorders. The National Academies Forum on Neuroscience and Nervous System Disorders hosted a public workshop in November 2023 to reflect on strategies to advance equitable practices in neuroscience and improve data quality by engaging more diverse populations in the research process; acknowledging systematic, technological, and internal biases; and considering inclusive research models.
Keywords: Health and Medicine

Engaging Scientists in Central Asia on Life Science Data Governance Principles: Proceedings of a Workshop Series - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
To facilitate scientific progress and collaboration while also protecting personal privacy, the integrity of research investments, and national security, it is important for life science data to be collected, digitized, secured, and shared responsibly. To exchange experiences and collaboratively discuss best practices for protecting life science data and promoting responsible data sharing in Central Asia, the U.S. National Academies of Sciences, Engineering, and Medicine convened a workshop series titled Engaging Scientists in Central Asia on Life Science Data Governance Principles, held virtually across six 2-hour sessions in May and June 2023. The workshop series brought together early-career and established scientists, along with experts in data science, cybersecurity, and law, from Kazakhstan, Kyrgyzstan, Tajikistan, the United States, Uzbekistan, and elsewhere to explore existing policies and practices, gaps and limitations, fundamental concepts relevant to data governance, and opportunities for improvement in data sharing practices and governance structures.
Keywords: Policy for Science and Technology; Biology and Life Sciences

Engaging Scientists in Central Asia on Life Science Data Governance Principles: Russian Version: Proceedings of a Workshop Series - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
To facilitate scientific progress and collaboration while also protecting personal privacy, the integrity of research investments, and national security, it is important for life science data to be collected, digitized, secured, and shared responsibly. To exchange experiences and collaboratively discuss best practices for protecting life science data and promoting responsible data sharing in Central Asia, the U.S. National Academies of Sciences, Engineering, and Medicine convened a workshop series titled Engaging Scientists in Central Asia on Life Science Data Governance Principles, held virtually across six 2-hour sessions in May and June 2023. The workshop series brought together early-career and established scientists, along with experts in data science, cybersecurity, and law, from Kazakhstan, Kyrgyzstan, Tajikistan, the United States, Uzbekistan, and elsewhere to explore existing policies and practices, gaps and limitations, fundamental concepts relevant to data governance, and opportunities for improvement in data sharing practices and governance structures.
Keywords: Policy for Science and Technology; Biology and Life Sciences

Exploring the Science on Measures of Body Composition, Body Fat Distribution, and Obesity: Proceedings of a Workshop Series - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
The National Academies Roundtable on Obesity Solutions hosted a public workshop series in April and June 2023 that explored the current science on measures of body composition and body fat distribution. Discussions focused on the strengths and limitations, and clinical and anthropological perspectives of body mass index (BMI) as a measure of adiposity and health. Presentations also shed light on the connection between misinformation and bias and stigma, as well as challenged current communication strategies to improve messaging about obesity.
Keywords: Food and Nutrition

Enhancing EPA Science Capability for a Complex Future: Recommendations for Use of Title 42 Special Hiring Authority - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
A scientific workforce with cutting-edge skills is critical for the ability of the U.S. Environmental Protection Agency to carry out its mission to protect human health by identifying environmental hazards, evaluating risks to public health and ecosystems, and formulating effective methods for pollution control and prevention. To aid in the selection and hiring of premier scientists and engineers, in 2006, EPA first sought the ability to directly recruit world-renowned scientists and engineers from academia, private industry, and other government agencies under Title 42, Section 209, of the U.S. Code. Title 42 authorizes federal agencies to appoint highly qualified scientists and engineers outside of standard civil service positions. Congress reauthorizes the EPA Title 42 authority in 5-year increments. To guide decisions about the future of the program, Congress asked the National Academies to review past and current EPA use of Title 42 hiring authority and how the program might be improved. The report finds that EPA has used its limited Title 42 authority effectively since 2006 and that Title 42 authority has enabled the hiring of effective scientific leadership and improved the scientific capability and capacity to support the Agency mission. Furthermore, the report finds that Title 42 can help the agency in addressing future environmental complexities. In continuing to enhance its scientific workforce and maintain a position at the forefront of evolving scientific knowledge, EPA would benefit from Congressional approval for permanent Title 42 authority.
Keywords: Environment and Environmental Studies

Building Capacity for the U.S. Mineral Resources Workforce: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
The extraction of mineral resources provides the raw materials necessary to produce the products and technologies on which the global economy depends, including green technologies essential for decarbonization. Mineral extraction requires expertise in a range of areas - including mineral resources identification, environmental evaluation, processing, and reclamation - but many of the U.S. academic programs that have historically educated the U.S. minerals workforce face significant challenges attracting students and maintaining financial viability. For some programs, enrollment dropped 60 percent from 2015 to 2023, despite a growing demand for a minerals workforce. The National Academies convened a workshop on January 23-24, 2024 to consider how the United States can build the capacity of federal and state agencies, academia, and the private sector to meet U.S. mineral workforce needs. Participants addressed the urgent need to attract more students, discussed a need to integrate new disciplines into curricula as the industry evolves, and identified multipronged approaches to help enhance overall retention and recruitment. This proceedings synthesizes the key suggestions presented by participants that universities, companies, and government agencies could take to enhance the recruitment, training, and retention of workers in the mineral resources industry.
Keywords: Earth Sciences; Industry and Labor

A New Vision for High-Quality Preschool Curriculum - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
A high-quality preschool education can foster critical development and learning that promotes joyful, affirming, and enriching learning opportunities that prepare children for success in school and life. While preschool programs generally provide emotionally supportive environments, their curricula often fall short in advancing learning in math, early literacy, and science, and lack the necessary support for multilingual learners emerging bilingualism. Additionally, access to high-quality, effective early learning experiences may be limited and inadequate based on factors such as a childs race, location, gender, language, identified disability, and socioeconomic status. A New Vision for High-Quality Preschool Curriculum examines preschool curriculum quality for children from ages three to five, with special attention to the needs of Black and Latine children, multilingual learners, children with disabilities and children experiencing poverty in the United States. The report articulates a vision for high-quality preschool curricula for all children, grounded in an equity and justice-oriented principles from inception to implementation and evaluation.
Keywords: Education

The Role of Advanced Computation, Predictive Technologies, and Big Data Analytics Related to Food and Nutrition Research: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
The National Academies Food and Nutrition Board hosted a hybrid public workshop in October 2023 to explore opportunities and challenges related to applying advanced computation, big data analytics, and high-performance computing, including artificial intelligence, machine learning, and deep learning, to support advances in food systems and nutrition research. Speakers discussed the appropriate use of evidence generated from these methods to inform food- and nutrition-related programs and policies.
Keywords: Food and Nutrition; Computers and Information Technology

Mentorship, Well-Being, and Professional Development in STEMM: Addressing the "Knowing-Doing Gap": Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Despite the significant contributions of graduate students and postdoctoral scholars to scientific research, the environments in which they work and learn often offer inconsistent mentorship and professional development opportunities and only intermittently address their mental, financial, and social well-being. To examine mentorship, well-being, and professional development and the challenge of translating existing mentorship theory into effective interventions, The Roundtable on Mentorship, Well-being, and Professional Development convened a workshop on November 1 and 2, 2023. This publication summarizes the presentation and discussion of the workshop.
Keywords: Education

Supporting Family Caregivers in STEMM: A Call to Action - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Family caregiving is not simply an outside obligation that has no bearing on the workings of academic science, technology, engineering, mathematics, and medicine (STEMM) as it affects the lives of so many people working and studying in colleges and universities around the country. Caregiving responsibilities often clash with ingrained norms in academic STEMM environments, which demand that STEMM students and workers demonstrate immense devotion to their fields and are always available and visibly working. Supporting Family Caregivers in STEMM describes the ways in which the labor and contributions of caregivers are often invisible and undervalued, with a specific focus on the academic STEMM ecosystem, including undergraduate and graduate students, postdoctoral scholars, resident physicians and other trainees, tenure-track and non-tenure-track faculty, staff, and researchers. This report reviews policies and practices that support caregivers, locally and nationally, and describes best practices in policy implementation and design. Supporting Family Caregivers in STEMM also highlights innovative practices and offers actionable recommendations to higher education institutions, public and private funders, and the federal government.
Keywords: Industry and Labor

National Plan for Health Workforce Well-Being - National Academy of Medicine (The National Academies Press, 2024)
In the United States, 54% of nurses and physicians, 60% of medical students and residents, and 61% of pharmacists have symptoms of burnout. Burnout is a long-standing issue and a fundamental barrier to professional well-being. It was further exacerbated by the COVID-19 pandemic. Health workers who find joy, fulfillment, and meaning in their work can engage on a deeper level with their patients, who are at the heart of health care. Thus, a thriving workforce is essential for delivering safe, high-quality, patient-centered care. The National Plan for Health Workforce Well-Being is intended to inspire collective action that focuses on changes needed across the health system and at the organizational level to improve the well-being of the health workforce. As a nation, we must redesign how health is delivered so that human connection is strengthened, health equity is achieved, and trust is restored. The National Plan’s vision is that patients are cared for by a health workforce that is thriving in an environment that fosters their well-being as they improve population health, enhance the care experience, reduce costs, and advance health equity; therefore, achieving the “quintuple aim.” Together, we can create a health system in which care is delivered joyfully and with meaning, by a committed team of all who work to advance health, in partnership with engaged patients and communities.
Keywords: Health and Medicine

The Role of Advanced Computation, Predictive Technologies, and Big Data Analytics in Food and Nutrition Research: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Artificial intelligence (AI), machine learning (ML), and deep learning (DL) are promising tools that can be used to develop algorithms to better understand and predict interactions between food- and nutrition-related data and health outcomes. Understanding that additional research is needed to identify areas where AI/ML is likely to have an impact, the National Academies Food and Nutrition Board hosted a public workshop in October 2023 to explore the future benefits and limitations of integrating big data and AI/ML tools into nutrition research. Participants also discussed issues related to diversity, equity, inclusion, bias, and privacy and the appropriate use of evidence generated from these new methods.
Keywords: Food and Nutrition; Computers and Information Technology

Greenhouse Gas Emissions from Wildland Fires: Toward Improved Monitoring, Modeling, and Management: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Climate change is fundamentally changing ecosystems and their fire conditions, and the 2023 fire season highlighted the urgency of developing and implementing solutions to address wildland fires. Wildland fires transfer carbon between the land and the atmosphere through emissions of greenhouse gases (GHGs), along with other gasses and particles. Though fires can be a natural part of healthy, evolving ecosystems, large, uncontrolled wildland fires can have devastating consequences to human health, communities, and biodiversity. Human-driven changes in wildland fire regimes have the potential to increase GHG emissions at a scale that could inhibit global efforts to achieve net-zero GHG emissions in the coming decades. The National Academies of Sciences, Engineering, and Medicine convened a workshop on September 13-15, 2023, to identify opportunities to improve measurements and model projections of GHG emissions from wildland fires and discuss management practices that could be incorporated into current and future action plans. Participants emphasized the importance of learning from historic and current Indigenous fire management practices and centering Indigenous voices and leadership across all stages of fire management. Different global ecosystems - particularly temperate, boreal, and tropical biomes - have been impacted by climate and land use changes where historical fire regimes and the carbon balance have been disrupted. However, discussions highlighted the diverse set of available regionally differentiated and ecosystem-appropriate mitigation strategies. With improved understanding of fires and their GHG emissions, better information for mitigation and management, and incorporation of wildfire GHG emissions into national accounting mechanisms, practitioners, communities, and decision makers will be better equipped to prepare, adapt, and respond to future wildland fires.
Keywords: Environment and Environmental Studies; Earth Sciences

Using Cooperative Automated Transportation Data for Freeway Operational Strategies - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Since the introduction of digital computers more than 50 years ago, continuous developments in computer technology, emerging data sources, and communications have created opportunities for operational strategies and performance measures to improve freeway network safety and mobility. NCHRP Research Report 1080: Using Cooperative Automated Transportation Data for Freeway Operational Strategies, from TRB's National Cooperative Highway Research Program, is an assessment of transportation operational scenarios and use cases where freeway operational strategies could be improved through the transmission of data between a transportation management system and the larger cooperative automated transportation system. Supplemental to the report is a source code archive, a PowerPoint presentation, and an Implementation Plan.
Keywords: Transportation and Infrastructure

Valuing America's Health: Aligning Financing to Reward Better Health and Well-Being - National Academy of Medicine (The National Academies Press, 2024)
The United States is experiencing a decline in life expectancy despite high health care spending due to a multitude of factors, including the COVID-19 pandemic, opioid epidemic, high burden of chronic disease, and systemic and structural inequities.A response proportional to this crisis is required. Valuing America's Health: Aligning Financing to Reward Better Health and Well-Being explores opportunities to transform the current health and health care system to one that promotes whole person and whole population health. The publication emphasizes the need for a bold vision and sustainable financing strategies to prioritize health and well-being for all. Authors of the publication highlight the importance of building a movement to prioritize health, repairing systemic failures, holding stakeholders accountable, controlling health care costs, incentivizing health promotion, adopting collaborative financing and policy-making approaches, and empowering individuals and communities in health decision-making.The way is clear; what is needed now is the will to move forward. Learn more about how to ensure our nation's health and health care system can support optimal health for all.
Keywords: Health and Medicine